Effectiveness of Nanoone Woman Underwear for Dysmenorrhea Management - Neoh, Choo-Aun; Wu, Lan-Shiang; Neoh, Karen; Neoh, Jessie; Chuang, Kenny (Highlights on Medicine and Medical Science Vol. 3, 2021)
The objectives of this research is to assess the efficacy of Nanoone Woman Underwear in the treatment of dysmenorrhea. The purpose of this study is to determine the observed change in menstrual pain intensity from baseline to after wearing Nanoone Woman Underwear in women with primary dysmenorrhea. The level of dysmenorrhea pain will be assessed using a VAS (visual analogue scale) ranging from zero (no pain) to ten (extreme pain). A VAS will be used to assess effectiveness at baseline, weeks 1-2, 5-6, and 9-10 of the study. The primary goal is to determine the mean change in menstrual pain intensity from baseline to the endpoint visit. The difference in mean change in menstrual pain intensity from baseline during each menstrual cycle will also be examined. Subjects would be requested to utilise the VAS scoring methodology to record their menstrual pain level on a given sheet every day during menstrual bleeding for three consecutive menstrual cycles in the house. Based on statistical analysis, the mean maximum pain level at the poster menstrual cycle was significantly lower than the prior menstrual cycle when compared to experienced menstrual pain intensity. In women with primary dysmenorrheal, the mean improvement in maximum pain level during the menstrual cycle was substantially lower after long wearing Nanoone Woman Underwear. As a result, after wearing Nanoone Woman Underwear for a long time, the extent of menstrual pain intensity improvement was greater.